Evidence for genetic anticipation in nodal osteoarthritis. Issue 9 (1st September 1998) - Wright, Gary D; Regan, Marian; Deighton, Chris M; Wallis, Gillian; Doherty, Michael
Abstract : OBJECTIVE: Evidence was sought for genetic anticipation (disease occurring at an earlier age in subsequent generations, with increasing severity) in nodal osteoarthritis (NOA). METHODS: Age at symptom onset and disease severity was compared within 30 parent/offspring pairs with NOA. Correlation between the offspring age of disease onset and the parental age at conception was also assessed. RESULTS: The age at onset of nodal symptoms was earlier in the offspring (43 years (95% confidence intervals (CI) 38 to 47) v 61 (CI 58 to 65); mean difference 18 years (CI 13 to 22): p< 0.001) as was large joint symptom onset (48 years (CI 41 to 55) v 67 (CI 61 to 73); mean difference 20 years (CI 13 to 27): p< 0.01). A negative correlation existed between age of offspring symptom onset and parental age at conception. Fifteen (50%) offspring had similar or more extensive disease than their parents. CONCLUSIONS: These results suggest genetic anticipation occurs in NOA and if confirmed a search for trinucleotide repeats is warranted.